2004
DOI: 10.1111/j.1524-4733.2004.71272.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Olanzapine, Risperidone, or Haloperidol on the Cost of Schizophrenia Care in a Medicaid Population

Abstract: Total costs of schizophrenia care associated with olanzapine, risperidone, or haloperidol were similar, but component costs differed. Relative to risperidone or haloperidol, olanzapine may have a higher acquisition cost, but may decrease inpatient costs and be associated with more optimal medication use patterns. Use of risperidone may also increase pharmacy costs and be associated with greater persistence, relative to haloperidol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
36
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 43 publications
13
36
1
Order By: Relevance
“…In the United States, olanzapine initiators were found to have more complex psychiatric histories than risperidone initiators including more pre-existing psychiatric comorbidities [20], more prior use of other classes of psychiatric medications [20,21], higher prior psychiatric inpatient costs [22], more previous treatment with clozapine [21,23,24], and more initial prescriptions from psychiatrists [24]. Consistent with these prior studies, olanzapine initiators in the current analysis were more likely to have diagnoses for manic episodes and had more prior antidepressant use.…”
Section: Discussionsupporting
confidence: 78%
“…In the United States, olanzapine initiators were found to have more complex psychiatric histories than risperidone initiators including more pre-existing psychiatric comorbidities [20], more prior use of other classes of psychiatric medications [20,21], higher prior psychiatric inpatient costs [22], more previous treatment with clozapine [21,23,24], and more initial prescriptions from psychiatrists [24]. Consistent with these prior studies, olanzapine initiators in the current analysis were more likely to have diagnoses for manic episodes and had more prior antidepressant use.…”
Section: Discussionsupporting
confidence: 78%
“…The study also found that patients using atypical antipsychotics achieved longer TTAD relative to patients using typical antipsychotics (TAP). These latter results were consistent with previous, more restrictive studies using either retrospective paid claims data [3][4][5] or data from prospective trials designed to more closely approximate real-world clinical practice [6,7].…”
Section: Introductionsupporting
confidence: 90%
“…Patients being treated with olanzapine were less likely to discontinue treatment during the first year (8.89% vs. 14.51%, P Ͻ 0.0001) and had more days of therapy in the first year (248 days vs. 211 days, P Ͻ 0.0001) than risperidone patients. Gibson et al [4] compared episodes of drug therapy for Michigan Medicaid patients with schizophrenia treated with olanzapine (n ϭ 458), risperidone (n ϭ 481) or haloperidol (n ϭ 252). A 6-month washout period was required between episodes using the same drug (a restart episode) and a 30-day washout period was required for the other study drugs (a delayed switching episode).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The belief that every medication and psychotherapy had its niche was actually seldom questioned until the past two decades, during which we have seen a veritable explosion of new medications, many of which are many times as expensive as their older counterparts. This has caused Medicaid expenditures for each patient with schizophrenia in one state system to go to an average of $15,000 per year [1]. Over this same period of time, "managed care" has penetrated many markets to the point that psychotherapies are also routinely questioned due to their "expense" or seemingly open-ended nature.…”
Section: Introductionmentioning
confidence: 99%